2021
DOI: 10.1007/s10096-021-04307-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of favipiravir in COVID-19: a live systematic review

Abstract: We performed a systematic review and meta-analysis for the effectiveness of Favipiravir on the fatality and the requirement of mechanical ventilation for the treatment of moderate to severe COVID-19 patients. We searched available literature and reported it by using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Until June 1, 2021, we searched PubMed, bioRxiv, medRxiv, ClinicalTrials.gov, Cochrane Central Register of Controlled Trials (CENTRAL), and Google Scholar by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 30 publications
2
40
0
2
Order By: Relevance
“…There is no evidence that favipiravir reduces mortality or the use of mechanical ventilation among moderate and severe COVID-19 patients. 46 Previous in silico study suggested, F-RTP, which is the active form of favipiravir binds to the RdRp active site of SARS-CoV-2, SARS-CoV, and MERS-CoV in the presence of agents and proteins. 47 Favipiravir is a purine nucleic acid analog licensed for the treatment of influenza since it efficiently inhibits influenza, norovirus, and Ebola viruses’ RNA-dependent RNA Polymerase (RdRp).…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence that favipiravir reduces mortality or the use of mechanical ventilation among moderate and severe COVID-19 patients. 46 Previous in silico study suggested, F-RTP, which is the active form of favipiravir binds to the RdRp active site of SARS-CoV-2, SARS-CoV, and MERS-CoV in the presence of agents and proteins. 47 Favipiravir is a purine nucleic acid analog licensed for the treatment of influenza since it efficiently inhibits influenza, norovirus, and Ebola viruses’ RNA-dependent RNA Polymerase (RdRp).…”
Section: Discussionmentioning
confidence: 99%
“…In general, favipiravir has shown a consistent safety profile with no significant adverse events compared to the no favipiravir group in the recommended dose range (6,11,14). While in terms of efficacy in moderate and severe COVID-19 conflicting results were reported (9)(10)(11). The initial endorsement of favipiravir was based on its effect to reduce viral clearance (14,15), however later in the pandemic, viral clearance was shown not to be the proper measure of medication effectiveness, with many patients continuing to have positive RT-PCR results even after complete recovery (9,16).…”
Section: Discussionmentioning
confidence: 99%
“…It has been given restricted authorization in several countries, including India and Russia, while it is under investigation in the USA, Japan and elsewhere (5). Although favipiravir is an oral medication that has shown positive clinical effects in milder cases of COVID-19 disease (6), its clinical effect in more advanced moderate and severe COVID-19 has been inconsistent and need more investigation (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, some nucleotide analogous, 29,30 also used against some retroviruses such as Human Immunodeficiency Virus (HIV), have been proposed for SARS-CoV-2 treatment and while they have shown interesting in vitro and in vivo efficiency their clinical use is strongly limited also by rather sever side-effects and a non-trivial pharmacokinetic and administration. Between the proposed nucleotide analogous inhibiting SARS-CoV-2, we may cite Remdesivir, 31 acting by impeding the RNA translocation, 32 which follows the inclusion of a new nucleotide to free the active site and slide along the template, and Favipiravir, 33,34 which instead directly inhibits the RNAP catalytic site. 35 While the structure of SARS-CoV-2 RNAP has been resolved, 24,35 also in presence of inhibitors, the studies focusing on the enzymatic mechanism from a molecular and biochemical point of view are rare.…”
Section: Introductionmentioning
confidence: 99%